Prevalence and Clinical Characteristics of False-Positive Aspergillus Galactomannan Test in Healthy Subjects and Patients with Hematologic Malignancies - Abe, Yoshiaki; Narita, Kentaro; Kobayashi, Hiroki; Kitadate, Akihiro; Takeuchi, Masami; Matsue, Kosei (Blood, 2018)
▪ Background: Monitoring of the Aspergillus galactomannan (GM) antigen is an useful tool for early diagnosis of aspergillosis, especially in patients with hematologic malignancies. However, one of the major limitations of this assay is false-positivity, which has been described in pediatric patients, patients with graft-versus-host disease, and those taking dietary GM or certain antibiotics. Only a few studies have shown high incidence of false-positive GM test results in patients with multiple myeloma (MM). Here we investigated the prevalence of false-positive GM test results in healthy subjects and in patients with hematologic malignancies. Methods: First, we analyzed the prevalence and distribution of false-positive GM test results in healthy subjects. Next, we retrospectively analyzed the prevalence and clinical characteristics of false-positive GM test results in consecutive patients with symptomatic MM diagnosed between 2006 and 2018 at Kameda Medical Center, Kamogawa, Japan, and compared these findings with those of our historical cohort of patients with hematologic malignancies other than plasma cell disorders (consecutive patients with non-Hodgkin lymphoma [NHL] and myelodysplastic syndrome [MDS]). Patients with clinical and/or imaging findings consistent with aspergillosis (e.g. sinopulmonary infection) were excluded from the analysis. Serum GM was measured using the double-sandwich enzyme-linked immunosorbent assay (Platelia, Bio-Rad, France) in all subjects before any use of antibiotics or anticancer agents. Serum GM test results were considered positive for optical index value of ≥0.5 in duplicate tests. Results: We enrolled 572 healthy subjects. The median age was 46 years (interquartile range [IQR]: 30-55 years), and 267 (46.7%) were men. We found a positive correlation between the GM antigen levels and age; GM antigen levels tended to be higher in older patients (Figure 1A), and the patients with false-positive GM results were significantly older than those without (median: 54 and 43 years, respectively; P<0.001). We also found that the GM levels were significantly higher in men than in women (P<0.001, Figure 2A); false-positive GM test results were more prevalent in men than in women (21.0% and 9.8%, respectively; P<0.001, Figure 2B). The number of patients with MM, NHL, and MDS was 244, 187, and 112, respectively. There was no inter-group difference in age across the three groups (median: 73, 73, and 74 years, respectively; P=0.95), whereas male patients were significantly more prevalent among patients with MDS (67.9%) and less prevalent among those with MM (46.7%) (P=0.031). Nevertheless, the patients with MM showed significantly higher GM antigen levels and a higher frequency of false-positive GM test results compared to those with NHL or MDS (Figure 3A and 3B). We further investigated the myeloma-related factors, which were associated with the high incidence of the false-positive GM test results in MM, and found that patients with IgG-type MM had significantly higher GM antigen levels and a significantly higher frequency of the false-positive GM test results than those with IgA-type or light-chain-only MM (Figure 4A and 4B). Among the patients with IgG-type MM, IgG levels in patients with positive GM test results were higher than those with negative GM test results, although the difference was not statistically significant (median: 5092.0 and 4559.5 mg/dL, respectively; P=0.10, Figure 5A), whereas no difference in IgG levels was detected between patients with positive and negative results on GM tests among non-IgG-type MM patients (Figure 5B). IgG levels in patients with positive GM test results were significantly higher than in those with negative results among both patients with NHL and MDS (P=0.013 and 0.041, respectively; Figure 6). Conclusions: Our findings revealed significantly high frequencies of false-positive GM test results in the elderly and in men among healthy subjects. We also found a significantly higher frequency of false-positive GM test results in patients with MM, especially in those with IgG-type myeloma, when compared with patients having lymphoid and myeloid neoplasia. These results indicated that careful interpretation of the GM test results may be required in these populations in the assessment of possible aspergillosis. Further studies are required to validate our results and elucidate the mechanisms of these phenomena. [Display omitted] No relevant conflicts of interest to declare.